METODE WAHYU DAN MUSYAWARAH PADA MASA NABI DALAM PENYELESAIAN KASUS NUSYUZ: ANALISIS NORMATIF-HISTORIS - Abdurahman Abdurahman; Nuril Khasyi'in (Program Studi Hukum Keluarga Islam STAI Al-Falah Banjarbaru, 2026)
Nusyuz (consensus) in marital relationships often triggers domestic conflict, leading to divorce if not handled appropriately. In the contemporary era, a reconstruction of conflict resolution methodology rooted in prophetic values ​​yet adaptive to current developments is necessary. This study aims to analyze efforts to address nusyuz during the time of the Prophet Muhammad (peace be upon him) through a normative-historical approach. The primary focus is on examining the integration of revelation as a moral-legal foundation and deliberation as an applicable method for resolving domestic conflict. This qualitative study, based on library research, analyzed hadith texts and the Prophetic sirah (religious texts) related to handling family conflict. The results indicate that revelation provides basic principles of justice, mutual benefit (mubadalah), and stages of humanistic conflict resolution. Meanwhile, deliberation was used by the Prophet (peace be upon him) as a means of empathetic dialogue to understand the root of the problem and find solutions that best benefit both parties. This approach proved effective during the Prophet's time and demonstrates significant alignment with modern family counseling models that emphasize empathetic communication, neutrality, and win-win solutions. These findings indicate that the method for resolving nusyuz (concerns) during the Prophet's era is highly relevant for adoption and integration as a contemporary Islamic family counseling model to reduce divorce rates.